2017
DOI: 10.1016/j.dci.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics and immune function in fish: new insights from omics technologies

Abstract: The interplay between nutrition and immune system is well recognised, however the true integration of research between nutrition, animal energy status and immune function is still far from clear. In fish nutrition, especially for species maintained in aquaculture, formulated feeds are significantly different from the natural diet with recent changes in nutrient sources, especially with protein and oil sources now being predominated by terrestrial derived ingredients. Additionally, many feeds are now incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
140
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(142 citation statements)
references
References 119 publications
2
140
0
Order By: Relevance
“…Indeed, juvenile fish of gilthead sea bream are able to grow fast and efficiently from early life stages until market size with practical diets containing <10% marine feed ingredients (Benedito‐Palos et al., ). However, carnivorous fish fed with little or no fish meal/fish oil diets have been shown to have a wide range of metabolic effects that, in addition to affecting growth performance, can also impact on health (Martin & Król, ; Torrecillas et al., ) or the nutritious value of seafood products as the most important source of omega‐3 in the human diet (Ballester‐Lozano, Benedito‐Palos, Mingarro, Navarro, & Pérez‐Sánchez, ; Ballester‐Lozano et al., ; Benedito‐Palos et al., ). The precise mechanisms for this disruption of fish health and welfare are not fully understood, although recent studies with extreme diet formulations pointed out in gilthead sea bream that dietary supplementation of plant‐based diets with sodium butyrate helps to prevent in long‐term feeding trials the inflammation of the intestinal epithelium, preserves the integrity of the intestinal barrier (Estensoro et al., ) and improves bacteria and parasite disease outcomes (Piazzon et al., , ).…”
Section: Plant‐based Diets Experimental Set‐up and Data Collectionmentioning
confidence: 99%
“…Indeed, juvenile fish of gilthead sea bream are able to grow fast and efficiently from early life stages until market size with practical diets containing <10% marine feed ingredients (Benedito‐Palos et al., ). However, carnivorous fish fed with little or no fish meal/fish oil diets have been shown to have a wide range of metabolic effects that, in addition to affecting growth performance, can also impact on health (Martin & Król, ; Torrecillas et al., ) or the nutritious value of seafood products as the most important source of omega‐3 in the human diet (Ballester‐Lozano, Benedito‐Palos, Mingarro, Navarro, & Pérez‐Sánchez, ; Ballester‐Lozano et al., ; Benedito‐Palos et al., ). The precise mechanisms for this disruption of fish health and welfare are not fully understood, although recent studies with extreme diet formulations pointed out in gilthead sea bream that dietary supplementation of plant‐based diets with sodium butyrate helps to prevent in long‐term feeding trials the inflammation of the intestinal epithelium, preserves the integrity of the intestinal barrier (Estensoro et al., ) and improves bacteria and parasite disease outcomes (Piazzon et al., , ).…”
Section: Plant‐based Diets Experimental Set‐up and Data Collectionmentioning
confidence: 99%
“…Arachidonic acid was confirmed to improve resistance to environmental stresses via its influence on lipid metabolism of gilthead sea bream and Senegalese sole (Alves et al, 2012;Martins et al, 2013). Many studies have demonstrated that resistance to environmental stresses in fish is associated with nutrient enrichment (Martin, & Kr ol, 2017;Reinling, Houde, & Verreault, 2017); however, similar studies using shrimp were insufficient.…”
mentioning
confidence: 99%
“…), in the evaluation of transcriptomic responses in the fish intestine (Martin et al . ), in fish nutrition and immune response studies (Martin and Król ), and identification of possible stress biomarker genes in trout (Rebi et al . ).…”
Section: Molecular Biology Identification Techniques and Their Applicmentioning
confidence: 99%
“…Several types of microarray are available, such as: printed, where probes between 25-80 bp are printed on a glass slide; in situ, where 20-24 bp probes are synthesized directly on the solid surface; high-density microarray, in which silica granules containing the probes are used, based on active hybridization in which the nucleotide transformation occurs by electric current; and the suspension microarray, in which suspension granules are used as support and flow cytometry is applied to identify granules and target molecules (Miller and Tang 2009). This technique has already been used in several studies regarding seafood, such as mass identification of fish species in a reaction (Kochzius et al 2008;Hellberg and Morrissey 2011), for identification of Vibrio species present in seafood (Chen et al 2011;Cariani et al 2012), in the evaluation of transcriptomic responses in the fish intestine (Martin et al 2016), in fish nutrition and immune response studies (Martin and Kr ol 2017), and identification of possible stress biomarker genes in trout (Rebi et al 2017).…”
Section: Microarray Platformmentioning
confidence: 99%